Glia: from 'just glue' to essential players in complex nervous systems: a comparative view from flies to mammals. (3rd April 2018) - Losada-Perez, Maria
Abstract: In the last years, glial cells have emerged as central players in the development and function of complex nervous systems. Therefore, the concept of glial cells has evolved from simple supporting cells to essential actors. The molecular mechanisms that govern glial functions are evolutionarily conserved from Drosophila to mammals, highlighting genetic similarities between these groups, as well as the great potential of Drosophila research for the understanding of human CNS. These similarities would imply a common phylogenetic origin of glia, even though there is a controversy at this point. This review addresses the existing literature on the evolutionary origin of glia and discusses whether or not insect and mammalian glia are homologous or analogous. Besides, this manuscript summarizes the main glial functions in the CNS and underscores the evolutionarily conserved molecular mechanisms between Drosophila and mammals. Finally, I also consider the current nomenclature and classification of glial cells to highlight the need for a consensus agreement and I propose an alternative nomenclature based on function that unifies Drosophila and mammalian glial types.